2020
DOI: 10.1038/s41593-020-0628-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Tumor necrosis factor overcomes immune evasion in p53-mutant medulloblastoma

Abstract: wrote the manuscript, which was revised and approved by all authors. COMPETING INTERESTSSanford Burnham Prebys Medical Discovery Institute has filed a patent application with R.J.W.-R., A.G. and C.F.W. listed as inventors. PCT application serial number PCT/US2018/048916 was filed on August 30, 2018, and is currently pending. This application covers the potential of p53 as a biomarker for responsiveness to T cell based immunotherapy, and the use of TNF receptor superfamily ligands to increase MHC expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Taking into account that mutp53 cells show low levels of MHC-I, this could represent an important barrier for T cell recognition. Recently, it has been proposed that low doses of TNF (Tumor Necrosis Factor) can rescue the expression of MHC, making mutp53 cancer cells more sensitive to immunological therapy (Garancher et al, 2020 ).…”
Section: Impact Of Mutp53 Gain-of-functionmentioning
confidence: 99%
“…Taking into account that mutp53 cells show low levels of MHC-I, this could represent an important barrier for T cell recognition. Recently, it has been proposed that low doses of TNF (Tumor Necrosis Factor) can rescue the expression of MHC, making mutp53 cancer cells more sensitive to immunological therapy (Garancher et al, 2020 ).…”
Section: Impact Of Mutp53 Gain-of-functionmentioning
confidence: 99%
“…The mechanistic study showed that this is due to the loss of expression of TAP1 and ERAP1, but tumor necrosis factor factor-alpha (TNF-α) agonists can rescue the expression of these proteins. Moreover, in vivo studies also supported the notion that the p53 null state plays a pivotal role in immune evasion, and TNF can reverse this phenotype [49].…”
Section: Cross-talk Between P53 and Mhci Pathwaymentioning
confidence: 67%
“…MYC is known to suppress checkpoint proteins PD-1 and CD47 ( 43 ) and MYC inhibition is found to re-express these proteins making these immunotherapies effective again ( 44 ). Recent animal studies further suggest that p53 depletion is suppressing major histocompatibility complex (MHC) class 1 presentation, which mediates T cell immune escape in MYC-driven medulloblastoma ( 45 ).…”
Section: Current Treatment Of Brain Tumorsmentioning
confidence: 99%